Komunikasi Inklusif dan Representasi Gender Non-Biner di Indonesia: Kajian Sistematis atas Strategi Bahasa dan Media dalam Ruang Publik - Nawaf, Azmi; Sazali, Hasan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The persistent bias in media representations of non-binary gender identities in Indonesia raises a critical question: to what extent are public media and language capable of fostering inclusive and equitable communication? This study seeks to examine how non-binary gender identities are constructed through language strategies in Indonesian media practices, and to evaluate the extent to which principles of inclusive communication are implemented or overlooked within public discourse. The primary objective of this research is to systematically analyze patterns of representation and linguistic strategies concerning non-binary identities, while critically assessing these practices through the lens of inclusive communication. Employing a Systematic Literature Review (SLR) with a qualitative approach, this study synthesizes relevant academic literature published between 2015 and 2025. The theoretical framework integrates Stuart Hall’s theory of representation, Judith Butler’s theory of gender performativity, and Foss and Pearson’s concept of inclusive communication. The findings reveal that media representations of non-binary identities in Indonesia remain predominantly stereotypical and exclusionary, reinforced by gender-biased language and a lack of institutional awareness regarding inclusivity. Mainstream media have yet to adopt gender-neutral editorial standards, with more affirming narratives primarily emerging from grassroots initiatives and alternative media spaces.